Pentingnya Pengucapan yang Jelas dari Orang Tua: Untuk Mengoptimalkan Fungsi Lobus Temporal pada Anak - Erni, Erni; khasisah, Fitri; Hawaniah, Aisyah (Lembaga Yasin AlSys, 2024)
The brain is the primary organ responsible for maintaining human physical and psychological balance from developmental stages in the womb, through infancy, childhood, adolescence, adulthood, and old age. The brain guides humans to exhibit positive and negative behaviors. It functions positively in a positive environment and negatively in a negative one. A newborn's brain weighs 370 grams, and by the age of three, it reaches 70% of the adult brain weight, approximately 1.2 to 1.4 kilograms (3 pounds). This brain development phase is known as the